Self-esteem in adolescents with low academic achievement assessed with the Rorschach Inkblots - Garrido-Lecca, Magally (1997)
The objective of the study was to determine if there were differences in the self-esteem of adolescents with low academic achievement as compared ro those with an average or high achievement. The participants were 60 adolescents, aged 13 to 16, of both sexes and with an average or high IQ . Thirty presented a low school achievement (study group) and 30 had a good achievement (contrast group). The WISC-R was administered to determine the IQ and the Rorschach lnkblots, using the CS uf Exner, to assess the self-esteem. The results showed that the Rorschach is a good instrument tu assess self-esteem. Likewise, there are significant differences in the self-esteem uf adolescents with low achievement due to emotional deficits, as compared to those with high achievement.